2004
DOI: 10.1038/sj.tpj.6500260
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in candidate genes: implications for the risk and treatment of idiopathic Parkinson's disease

Abstract: Idiopathic Parkinson's disease (IPD) is a progressive neurodegenerative disorder for which no restorative or neuroprotective therapy is available. Interest has recently been directed to association studies on polymorphisms of various genes, mainly those related to dopamine metabolism and transport, and their effect on response to PD, which includes primarily levodopa and dopaminomimetics. Approximately 15-20% of patients with PD do not respond to levodopa, and the majority of those who do respond develop adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 189 publications
(202 reference statements)
0
17
0
2
Order By: Relevance
“…Since the duration and amplitude of dopamine action is determined by a rapid release of extracellular dopamine into presynaptic terminals, studies have suggested that polymorphisms in genes related to degradation and reuptake of dopamine could be involved in the risk of adverse outcomes after long‐term administration of levodopa or other dopaminergic drugs . Although side effects such as dyskinesia and motor fluctuations may severely impair the daily life of patients with PD some of these patients will never develop these effects …”
Section: Discussionmentioning
confidence: 99%
“…Since the duration and amplitude of dopamine action is determined by a rapid release of extracellular dopamine into presynaptic terminals, studies have suggested that polymorphisms in genes related to degradation and reuptake of dopamine could be involved in the risk of adverse outcomes after long‐term administration of levodopa or other dopaminergic drugs . Although side effects such as dyskinesia and motor fluctuations may severely impair the daily life of patients with PD some of these patients will never develop these effects …”
Section: Discussionmentioning
confidence: 99%
“…PD patients with early disease onset have a high probability to carry mutations for monogenic PD forms, and therefore, early onset and genetic predisposition are two overlapping and possibly interrelated risk factors. Other risk factors associated with increased risk of dyskinesias are female gender [17, 18] and the occurrence of specific polymorphisms for dopamine receptors or dopamine transporters [1921]. …”
Section: Epidemiology and Clinical Aspects Of Motor Complicationsmentioning
confidence: 99%
“…PD patients with early disease onset have a high probability to carry mutations for monogenic PD forms and therefore early onset and genetic predisposition are two overlapping and possibly interrelated risk factors. Other risk factors associated with increased risk of dyskinesias are female gender [50,86] and the occurrence of specific polymorphisms for dopamine receptors or dopamine transporters [29,36,68].…”
mentioning
confidence: 99%